An infrequently encountered case of spontaneous subcapsular liver hematoma with hepatic artery pseudoaneurysm - Daniel Joh; Munish Sharma; Mehrunissa Taj; Salim Surani (Greater Baltimore Medical Center, 2021)
Hepatic artery pseudoaneurysm (HAP) is a rare complication of liver trauma and liver transplant, and spontaneous subcapsular liver hematoma is not frequently encountered outside the setting of preeclampsia and hemolysis, elevated liver enzyme and low platelet (HELLP) syndrome. We report a rare case of spontaneous subcapsular liver hematoma with hepatic artery pseudoaneurysm without any apparent liver trauma or recent interventional procedures of the hepatobiliary system. Although subcapsular hepatic hematoma and HAP are uncommon diagnoses, clinicians should be aware of these diagnoses to promptly diagnose and effectively treat them. Clinicians should also not forget these diseases could be masked by other common etiologies, such as gastritis.